PROFIL TINGKAT KETERAMPILAN BERMAIN BULUTANGKIS ATLET USIA 10-12 TAHUN PB. MUTIARA BANDUNG - Megantara, Surya Medal (Jurnal Olahraga, 2015)
Badminton is much favored by various groups and walks of life, ranging from children to adults and even parents. This can be proven by the many uses of the field and is marked by the establishment of clubs both from government and private institutions and has been developed in sports coaching centers such as coaching in West Java, especially like SGSE, Mutiara Bandung, PR Tasikmalaya, KOTAB, FPOK and other clubs. In the world of sports, achievement is very important. What is achieved at this level will be the basis for determining the possibility of entering the next level of achievement that is better or to pursue a career on the world stage. In an effort to improve the performance of badminton requires a systematic and continuous coaching that is programmed in the long term and starts with early age coaching. This is driven by the need to create an athlete who can excel at the international level. The problem that arises in this study is to find out how much the level of badminton playing skills in athletes aged 10-12 years in PB. Bandung Pearls. The method in this research is descriptive method, in this method the author uses a measuring instrument in the form of a test of badminton playing skills. The population and sample used are athletes aged 10-12 years in PB. Bandung Pearls. The results of this study are expected to provide meaningful input for coaches and coaches regarding the level of badminton playing skills that are expected when they want their students to be more achievers and become winners in badminton matches at the age of 10-12 years